2017
DOI: 10.1039/c7ta00353f
|View full text |Cite
|
Sign up to set email alerts
|

Selective electro- or photo-reduction of carbon dioxide to formic acid using a Cu–Zn alloy catalyst

Abstract: A copper-and-zinc (Cu–Zn) alloy material was synthesized using a vacuum sealing method, in which evaporated zinc was reacted with copper film or nanoparticles to form a homogeneous Cu–Zn alloy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 58 publications
2
61
0
Order By: Relevance
“…The competitive interaction of H + /water with two metal centers may tune the binding strength of intermediates and control the reaction pathway to accelerate the reaction rate of CO 2 reduction on the surface. A few recipes of alloying have been developed for the synthesis of Cu‐based or Sn‐based electrocatalysts for CO 2 RR, including CuPd, CuPt, CuAu, CuAg, CuIn, CuZn, CuSn, SnAg, SnPd, SnPb, etc. For CuSn bimetallic systems as a kind of potential catalysts, previous research works have shown that the control of their composition provided a promising approach for improving the electrocatalytic properties for CO 2 reduction .…”
Section: Introductionmentioning
confidence: 99%
“…The competitive interaction of H + /water with two metal centers may tune the binding strength of intermediates and control the reaction pathway to accelerate the reaction rate of CO 2 reduction on the surface. A few recipes of alloying have been developed for the synthesis of Cu‐based or Sn‐based electrocatalysts for CO 2 RR, including CuPd, CuPt, CuAu, CuAg, CuIn, CuZn, CuSn, SnAg, SnPd, SnPb, etc. For CuSn bimetallic systems as a kind of potential catalysts, previous research works have shown that the control of their composition provided a promising approach for improving the electrocatalytic properties for CO 2 reduction .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the higher TON was recorded to be 1400 in the case of our Cu-Zn/SrTiO 3 under UV irradiation. 18 These results strongly suggest that our Z-scheme system is highly stable under photon irradiation in aqueous media. The quantum efficiency for the reduction products was 0.14% in our system.…”
mentioning
confidence: 58%
“…However, highly selected HCOOH generation has only been achieved by using expensive noble metal-complexes to date. 17 In contrast, in our previous research, copper and zinc based bulk alloys were investigated as electrocatalysts for HCOOH production, 18 but they could not be applied in photocatalysis or photo-electrochemical systems because of their bulk form and/or high temperature preparation conditions.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, the higher concentrations of Cu 2+ are reported to be responsible for diseases such as Menkes, Wilson‘s Parkinson's while that of Zn 2+ for ischemia, seizures, and Alzheimer's etc . These two metal ions have also a wide range of applications in the field of chemistry as important constituent of various chemicals including catalysts as well as electrodes . In the light of their wide spectrum applications of Cu 2+ and Zn 2+ , their accurate and easy marking is one of the important tasks for the practitioners of chemistry ranging from academics to industries.…”
Section: Introductionmentioning
confidence: 99%